PERANAN BUDAYA ORGANISASI DALAM MEMBANGUN LOYALITAS KARYAWAN: STUDI KASUS GRAND HYATT JAKARTA - Yustisia Pasfatima Mbulu; Daniel Widjaja; Sarfilianty Anggiani (Fakultas Pariwisata Universitas Pancasila, 2021)
This study aims to analyze the role of organizational culture at the Grand Hyatt Jakarta and to analyze employee loyalty at the Grand Hyatt Jakarta and the impact of organizational culture on employee loyalty at the Grand Hyatt Jakarta. The method used in this research is a qualitative descriptive case study using primary and secondary data. The results of this study indicate that the role of organizational culture at Grand Hyatt Jakarta is seen from the indicators of organizational culture characteristics which consist of seven elements, but one element is still being considered, namely the elements of innovation and risk taking. For employee loyalty at the Grand Hyatt Jakarta, it can be seen from the four indicators that only one indicator is still being considered, namely the compliance indicator. While the impact of organizational culture on employee loyalty at Grand Hyatt Jakarta can be seen that from the indicators of innovation and risk taking, results orientation, orientation to human resources and orientation to the team have an impact on employee responsibility. The indicators of attention to detail or detail will increase the level of employee compliance and the indicators of aggressiveness will make employees have dedication to the hotel as well as indicators of stability / stability which will make employees have integrity.